THE USAGE OF STYLISTIC DEVICES IN LITERARY WORKS - Усманов Ф.М.; Рустамова Ф.Р. (Journal of new century innovations, 2024)
Abstract: The use of stylistic devices in literary works is a fundamental aspect of creative writing that enhances the depth and impact of the text. This article explores the significance of stylistic devices such as metaphors, similes, imagery, and symbolism in shaping the tone, mood, and overall aesthetics of literary compositions. By delving into the intricacies of these devices, writers can evoke emotions, create vivid imagery, and convey complex ideas with finesse. Through a detailed analysis of selected works across various genres, this article highlights how authors strategically employ stylistic devices to engage readers on intellectual and emotional levels. Furthermore, the article discusses how the choice of specific devices can reflect the author's voice, thematic concerns, and narrative intentions.